A Partial Nested Decomposition Approach for Remanufacturing Planning Under Uncertainty - Quezada-Valenzuela, F (Springer Science and Business Media Deutschland GmbH, 2021)
We seek to optimize the production planning of a three-echelon remanufacturing system under uncertain input data. We consider a multi-stage stochastic integer programming approach and use scenario trees to represent the uncertain information structure. We introduce a new dynamic programming formulation that relies on a partial nested decomposition of the scenario tree. We then propose a new extension of the recently published stochastic dual dynamic integer programming algorithm based on this partial decomposition. Our numerical results show that the proposed solution approach is able to provide near-optimal solutions for large-size instances with a reasonable computational effort. © 2021, IFIP International Federation for Information Processing.